Converts from infidelity;: or, Lives of eminent individuals who have renounced libertine principles and sceptical opinions, and embraced Christianity - Crichton, Andrew (Constable's miscellany of original and selected Publications, 1827)
Vol. 1. - John Wilmot, Earl of Rochester; Count Struensee; Count Brandt; Lord Lyttelton; Sir John Pringle; Gilbert West; Charles Gildon; Richard Cecil.- Vol. 2. - Hon. Robert Boyle; Captain James Wilson; Soame Jenyns; Dr. Thomas Bateman; Baron Haller; Rev. John Newton; M. De La Harpe; John Bunyan.